Analysis of Elementary School Selection Factors During Pandemic - Kartika Rinakit Adhe; Wiryanto Wiryanto; Suryanti Suryanti; Nenny Chanidatus Shofiyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
School selection has always been a problem for parents to get the best school for their children, especially during a pandemic. The purpose of this study was to describe the factors for selecting primary schools during the pandemic. This study uses a qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation. The sample in this study was spread from the Gresik, Surabaya and Sidoarjo areas with a total of 15 parents. This research used Milles and Huberman analysis technique. The results of the study describe the factors of parents in choosing schools during the pandemic. The findings of this study are that there are many factors that influence parents in choosing elementary schools for their children, including 1. Location or distance 2. Environment 3. Circumstances 4. School status 5. Teacher background at school 6. Costs 7. Social and economic status of parents. And based on the results of the research, the distance factor that most influences parents in choosing a school. When viewed from the school status of the 15 parents, there were 13 parents who chose to send their children to private schools. So the findings from this study are that parents are not currently concerned about the cost of schooling their children, but rather the quality and distance between school and home.